LY354740 Reduces Extracellular Glutamate Concentration, Inhibits Phosphorylation of Fyn/NMDARs, and Expression of PLK2/pS129 α-Synuclein in Mice Treated With Acute or Sub-Acute MPTP - Tan, Yang; Xu, Yan; Cheng, Chi; Zheng, Cong; Zeng, Weiqi; Wang, Ji; Zhang, Xiaoqian; Yang, Xiaoman; Wang, Jialing; Yang, Xiaomei; Nie, Shuke; Cao, Xuebing (Frontiers in Pharmacology, 2020)
Glutamate overactivity in basal ganglia critically contributes to the exacerbation of dopaminergic neuron degeneration in Parkinson’s disease (PD). Activation of group II metabotropic glutamate receptors (mGluRII or mGluR2/3), which can decrease excitatory glutamate neurotransmission, provides an opportunity to slow down the degeneration of the dopaminergic system. However, the roles of mGluR2/3 in relation to PD pathology were partially recognized. By using mGluR2/3 agonist (LY354740) and mGluR2/3 antagonist (LY341495) in mice challenged with different cumulative doses of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), we demonstrated that systemic injection of LY354740 reduced the level of extracellular glutamate and the extent of nigro-striatal degeneration in both acute and sub-acute MPTP mice, while LY341495 amplified the lesions in sub-acute MPTP mice only. LY354740 treatment improved behavioral dysfunctions mainly in acute MPTP mice and LY341495 treatment seemed to aggravate motor deficits in sub-acute MPTP mice. In addition, ligands of mGluR2/3 also influenced the total amount of glutamate and dopamine in brain tissue. Interestingly, compared with normal mice, MPTP-treated mice abnormally up-regulated the expression of polo-like kinase 2 (PLK2)/pS129 α-synuclein and phosphorylation of Fyn/N-methyl-D-aspartate receptor subunit 2A/2B (GluN2A/2B). Both acute and sub-acute MPTP mice treated with LY354740 dose-dependently reduced all the above abnormal expression. Compared with MPTP mice treated with vehicle, mice pretreated with LY341495 exhibited much higher expression of p-Fyn Tyr416/p-GluN2B Tyr1472 and PLK2/pS129 α-synuclein in sub-acute MPTP mice models. Thus, our current data indicated that mGluR2/3 ligands could influence MPTP-induced toxicity, which supported a role for mGluR2/3 in PD pathogenesis.